Chemotherapy by intravenous administration of conjugates of daunomycin with monoclonal and conventional anti-rat alpha-fetoprotein antibodies. - Tsukada, Y (1982)
Monoclonal antibodies to rat alpha-fetoprotein (AFP) were produced by hybridization of mouse myeloma cells with spleen cells from mice immunized with rat AFP. The monoclonal antibodies as well as horse anti-rat AFP were coupled via a dextran bridge to daunomycin. Both types of conjugates were tested in vitro and in vivo for their anti-tumor activity. They were equally cytotoxic to rat AH66 hepatoma cell line in culture. Rats challenged with hepatoma cells were treated with the conjugates either by intraperitoneal or intravenous injections. Daunomycin conjugates with horse anti-AFP and monoclonal mouse anti-AFP were capable of delaying the tumor development more efficiently than the controls of antibodies or free drug, mixtures of drug with antibodies, and a conjugate of drug and normal immunoglobulin. The specific conjugates were considerably more effective when the treatments were given intravenously. The specific conjugates produced 60% long-term survival, whereas the controls delayed only slightly tumor development.